Platelet function monitoring for stent thrombosis in critically III patients with an acute Coronary syndrome. (6th December 2017) - Tilemann, Lisa; Mohr, Sarah K.; Preusch, Michael; Chorianopoulos, Emanuel; Giannitsis, Evangelos; Katus, Hugo A.; Müller, Oliver J.
Abstract : Background: Patients after cardiac arrest or in cardiogenic shock due to acute coronary syndrome (ACS) are at high risk for stent thrombosis (ST) and recurrent cardiovascular events after primary percutaneous coronary intervention (PCI). High post‐interventional platelet reactivity (HPR) might be an additional risk factor for ST in these critically ill patients. Methods: Between 2006 and 2016, 401 critically ill patients from a cardiologic intensive care unit underwent platelet function testing after primary PCI using whole blood impedance aggregometry. After exclusion of patients with an abnormal platelet count, 357 patients have been included into the final analysis of this retrospective observational study. Results: The incidence of definite early ST was 19.2% in patients with HPR to P2Y12 antagonists and 1.2% in patients without HPR. Likewise, the incidence of early ST in patients with HPR to acetylsalicylic acid (ASA) was 21.4% versus 1.8% in patients without HPR. In contrast, the incidence of late ST or recurrent myocardial infarction in untreated lesions was not associated with HPR to ASA or P2Y12 antagonists. Conclusions: Platelet function testing in critically ill ACS patients identified patients at high risk for early ST and might be beneficial for risk stratification.